Development of high performance and defect-free asymmetric polyethersulfone membranes for O2/N2 separation [electronic resource] - 304370 Norida Ridzuan (Skudai : Universiti Teknologi Malaysia, 2004)
Thesis (Sarjana Kejuruteraan (Gas)) - Universiti Teknologi Malaysia, 2004